Предмет: Алгебра,
автор: Ludmila14
Помогите решить уравнение
(х-5)(х-2)-(х+1)(х-4)=6
Ответы
Автор ответа:
0
x²-2x-5x+10-(x²-4x+x-4)=6
x²-2x-5x+10-(x²-3x-4)=6
x²-2x-5x+10-x²+3x+4=6
-4x+14=6
-4x=6-14
-4x=-8
x=-8:(-4)
x=2
x²-2x-5x+10-(x²-3x-4)=6
x²-2x-5x+10-x²+3x+4=6
-4x+14=6
-4x=6-14
-4x=-8
x=-8:(-4)
x=2
Похожие вопросы
Предмет: Математика,
автор: yuliyashirokova
Предмет: Математика,
автор: raccoon1888
Предмет: География,
автор: tttadelina
Предмет: Математика,
автор: Полинка432
Предмет: Алгебра,
автор: eseniz